Akulturasi Budaya Islam – Kristen dalam Meujudkan Kerukunan - Hamdani AG (IAIN Padangsidimpuan, 2016)
Acculturation is a process of change (integration) between culture and psychology as a result of relationship of two or more cultural groups within the members of their culture. Acculturation allows the birth of a new cultural diversity that can be accepted by all members of multiethnic communities, not least the cultural heritage of certain ethnic, creativity or initiative outcomes and culture coming from the outside. Acculturation is able to knit the harmonization of social and religious harmony among multireligious society, based on mutual respect and respecting others. Because of acculturation integrate all cultural subcultures such as customs, traditions, language, art, values and norms, education and livelihood, except the matter of aqidah (faith) that impossible to be acculturated. Subdistrict Community Besitang, Langkat, and North Sumatra comprising Malays, Javanese, Acehnese and Minangkabau Muslim and Karo and Batak Christians have managed to reach the level of the most successful acculturation. Muslim and Christian leaders, as well Muspika Harmony Forum (FKUB) highly committed local creating a harmonious atmosphere and religious harmony in the community, through the cultural approach to all ethnic groups. This proved able to create a safe atmosphere, peace, and harmony without social conflict in the middle of the multiethnic and multireligious society.